Regulation of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Activity in Human Fibroblasts by Lipoproteins - Brown, Michael S. (1973)
The activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase (EC 1.1.1.34), the rate-limiting enzyme of hepatic cholesterol biosynthesis, is suppressed in human fibroblasts cultured in the presence of serum. This enzyme activity increases by more than 10-fold after the removal of serum from the medium. The rise in enzyme activity requires de novo protein synthesis and is not accompanied by changes in the activities of several other cellular enzymes. The factor responsible for the suppression of 3-hydroxy-3-methylglutaryl coenzyme A reductase activity in cultured fibroblasts is present in the sera of at least four mammalian species, and in human serum it is found in the low-density lipoproteins. Human high-density lipoproteins, very low-density lipoproteins from chicken egg yolk, and the fraction of human serum containing no lipoproteins do not suppress the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase.